Occlusal therapy in patients with temporomandibular joint dysfunction and occlusal and articulatory disorders - Chervonna , Nadiya; Proschenko , Andriy; Proschenko , Nina (The Ukrainian Scientific Medical Youth Journal, 2024)
the article presents a statistical analysis of the assessment of the impact of various factors that led to occlusal and articulatory disorders and functional disorders of the masticatory apparatus on the choice of occlusal constructions therapy for the treatment of temporomandibular joint dysfunction. For conducting the research, a clinical and laboratory examination was carried out and orthopedic treatment of 150 patients with various occlusal options violations Variants of occlusion therapy are described and given characteristic.